Sushi and beyond what the Japanese know about cooking - Booth, Michael
Japan is the pre-eminent food nation on earth. The creativity of the Japanese, their dedication and ingenuity, not to mention courage in the face of dishes such as cod sperm and octopus ice cream, is only now beginning to be fully appreciated in the sushi-saturated West, as are the remarkable health benefits of the traditional Japanese diet.